2019
DOI: 10.1029/2018ja026333
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral and Multi‐instrument Observation of TIDs Following the Total Solar Eclipse of 21 August 2017

Abstract: Wave‐like structures in the upper atmospheric nightglow brightness were observed on the night of 22 August 2017, approximately 8 hr following a total solar eclipse. These wave‐like perturbations are signatures of atmospheric gravity waves and associated traveling ionospheric disturbances (TIDs). Observations were made in the red line (OI 630.0 nm) and the green line (OI 557.7 nm) from Carbondale, IL, at 2–10 UTC on 22 August 2017. Based on wavelet analyses, the dominant time period in both the red and green li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The above mentioned authors also detected depletions and enhancements at the 10.1029/2020JA027923 Journal of Geophysical Research: Space Physics geomagnetic conjugate locations of the eclipse in the Southern Hemisphere using this methodology, in concordance with the results of Huba and Drob (2017). Some modeling and observational studies (Aryal et al, 2019;Lei et al, 2018) concentrated on the posteclipse ionospheric response. Lei et al (2018) found small global average TEC perturbations (0.2 TECu) 9 hr after an eclipse.…”
Section: Journal Of Geophysical Research: Space Physicssupporting
confidence: 71%
See 1 more Smart Citation
“…The above mentioned authors also detected depletions and enhancements at the 10.1029/2020JA027923 Journal of Geophysical Research: Space Physics geomagnetic conjugate locations of the eclipse in the Southern Hemisphere using this methodology, in concordance with the results of Huba and Drob (2017). Some modeling and observational studies (Aryal et al, 2019;Lei et al, 2018) concentrated on the posteclipse ionospheric response. Lei et al (2018) found small global average TEC perturbations (0.2 TECu) 9 hr after an eclipse.…”
Section: Journal Of Geophysical Research: Space Physicssupporting
confidence: 71%
“…Lei et al (2018) found small global average TEC perturbations (0.2 TECu) 9 hr after an eclipse. Alternatively, multiinstrument (GNSS TEC and digisonde) and spectral observations (OI emissions) led Aryal et al (2019) to conclude that it is the prevalent geomagnetic disturbance via enhanced auroral currents/Joule heating that generates AGWs and large-scale traveling ionospheric disturbances (LSTIDs) propagating toward the equator. GITM results show that the associated 10% increases in N and O/N 2 at 250 km present oscillations of 90 min with vertical speeds and wavelengths of 7 m s −1 and 36 km, respectively, and 616 m s −1 and 1,256 km.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…Their position does not correspond to thunderstorms occurring during the eclipse ((Mrak, Semeter, Nishimura, et al, )), but around 18:00 UT the position corresponds to that of EUV modulations shown by (Mrak, Semeter, Drob, et al, ). (Aryal et al, ) show that increased geomagnetic activity after the eclipse generated large scale TIDs with a wavelength of more than 1,000 km and a dominant period of 1.5 hr. As our choice of the grid limits the FFT resolution to a maximum wavelength of 600 km we cannot see TIDs of the same type during the day, although Box 4 lies within the same period.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of these changes in the atmospheric composition and dynamics, large-scale disturbances (TIDs) were observed in the ionosphere associated with the eclipse (e.g., Coster et al, 2017). Finally, a wave-like signature of the bow wave generated by the eclipse was observed in the neutral winds by a Fabry-Perot interferometer over São João do Cariri (Harding et al, 2018) and over Carbondale (37.7 o N, 89.2 o W) using airglow red and green lines (Aryal et al, 2019).…”
Section: Discussionmentioning
confidence: 93%